Field-induced metamagnetism transition with anisotropic magnetoresistance in helical magnetic order on MnRuP single crystals - W. Wu; W. J. Guo; P. Zheng; Zh. Li; G. Li; J. L. Luo (Physical Review Research, 2023)
Measurements of physical properties, including transport and magnetic properties and thermal conductivity, have been performed on single crystal MnRuP with helical magnetism structure. A field-induced first-order metamagnetism transition with a magnetization jump is discovered when the magnetic field is applied perpendicular to the c axis. The arising transition is a result of the competition between magnetic energy and elastic energy with a complex noncollinear character in the vicinity of the metastable state in MnRuP, which is due to the transition from the incommensurate helical phase to the commensurate Yafet-Kittel ferrimagnetic phase or from the helical phase to the conical phase. It is worthwhile to note that both negative and positive magnetoresistance (MR) are observed when the field is parallel or perpendicular to the electric current, respectively, which is rarely found in the other system simultaneously. Such positive MR is unexpected on the basis that the application of magnetic field should favor a low-resistive state due to alignment of spins. The ability to manipulate magnetic properties with current directions may pave the way to a new method of realizing magnetic memories based on the spin internal degrees of freedom.